The Hospital Ethics Committee: Health Care's Moral Conscience or White Elephant? - Blake, David C. (The Hastings Center report, 1992)
In a morally fragmented society there is no good reason for ethics committees to assume any particular point of view, yet failure to do so compromises their ability to function in either a case-review or an educational capacity. A casuist methodology might enable committees to fulfill both roles.